Effectiveness of Think-Pair-Share Technique towards Speaking Skills in Giving and Asking Opinions - Istiadi , Nabila Yumna; Yuliati, Yuliati; Hutagalung, Fonny Dameaty; Seinsiani, Izzati Gemi (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2025)
Effective speaking skills are crucial for academic success and future professional opportunities, making their development a key focus in educational settings. This research investigates the Think-Pair-Share (TPS) technique effectiveness in improving students’ speaking skills in giving and asking for opinions, addressing a significant need for practical cooperative learning strategies. This study used quantitative approach with quasi-experimental designs involving 68 eleventh-grade students in total at SMA Negeri 15 Semarang in the second semester of the 2023/2024 academic year, divided into two groups: an experimental group (n=35) and a control group (n=33). Both groups were given a pre-test, followed by treatments with three meetings in each. After the treatments, a post-test was administered to determine the effectiveness. Based on the data, the control group’s, taught using the group discussion achieved an average score of 72.36 and the experimental group, taught using the TPS techniqe, scored 86.17. The experimental group’s N-Gain score was 62.29, which is classified as